2009
DOI: 10.1002/cbic.200800539
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Synthesis of New Cyclodepsipeptides of the PF1022‐Type: Probing the α‐D‐Hydroxy Acid Tolerance of PF1022 Synthetase

Abstract: The nonribosomal peptide synthetase PF1022-synthetase (PFSYN) synthesises the cyclooctadepsipeptide PF1022 from the building blocks D-lactate, D-phenyllactate and N-methylleucine. The substrate tolerance of PFSYN for hydroxy acids was probed by in vitro screening of a set of aliphatic and aromatic alpha-D-hydroxy acids with various structural modifications in the side chain. Thus, new PF1022 derivatives for example, propargyl-D-lactyl-PF1022 and beta-thienyl-D-lactyl-PF1022 were generated. The promiscuous beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 20 publications
0
46
0
3
Order By: Relevance
“…The in vitro reconstitution of complete NRPS pathways 40 has been reported for only a handful of natural products including cyclooctadepsipeptide PF1022, 41, 42 pacidamycin, 43 antimycin, 44 beauvericins, 45 and the siderophore synthesis pathways involved in production of enterobactin, 46 yersiniabactin, 47 pyochelin, 48 vibriobactin, 49 myxochelin, 16 and pseudomonine. 50 Biosynthesis of the indole alkaloid terrequinone, which uses a noncanonical monomodular NRPS for dimerization of a tryptophan derivative, was also reconstituted in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro reconstitution of complete NRPS pathways 40 has been reported for only a handful of natural products including cyclooctadepsipeptide PF1022, 41, 42 pacidamycin, 43 antimycin, 44 beauvericins, 45 and the siderophore synthesis pathways involved in production of enterobactin, 46 yersiniabactin, 47 pyochelin, 48 vibriobactin, 49 myxochelin, 16 and pseudomonine. 50 Biosynthesis of the indole alkaloid terrequinone, which uses a noncanonical monomodular NRPS for dimerization of a tryptophan derivative, was also reconstituted in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several published total syntheses in solution and an in vitro synthesis approach, only a limited number of PF1022A derivatives have become available. [5,[8][9][10] Remarkably, until now only a partial solid-phase synthesis of PF1022 analogues has been hydroxycarboxylic acids. We report herein an efficient synthesis of the anthelmintic PF1022A and its commercial analogue emodepside on Kaiser and Wang resins.…”
Section: Introductionmentioning
confidence: 99%
“…18 Previous studies of enzymatic synthesis of CODs with related fungal NRPSs indicated a relaxed substrate specificity for the hydroxy acid-activating A 1 domain, whereas amino acid activation was apparently more restricted. 19,20 Application of these observations to in vivo biosynthesis with fungal cultures led to the isolation of new CODs of the enniatin, 21 the PF1022 and the beauvericin series. 22,23 Beauvericin synthetase BbBEAS was isolated from E. coli BL21 bbBeas + (for cultivation conditions see ESIw, General techniques) by precipitation with 60% ammonium sulphate as described recently for related COD synthetases.…”
mentioning
confidence: 99%